Praktik Pertanian Pangan Masyarakat Sedulur Sikep: Negosiasi antara Nilai Kultural terhadap Tuntutan Pasar - Dwi Sartika; Gunawan Gunawan (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
Food farming practices among the Sedulur Sikep community are grounded in cultural values that emphasize the sustainability of human nature relations and subsistence-based livelihood fulfillment. However, when agricultural products enter market distribution chains, farmers encounter marketing constraints and price disparities due to incompatibility with modern market mechanisms. This tension encourages adjustments in food farming practices through the selective adoption of semi-organic systems as a form of negotiation with market demands. This study draws on Mark Granovetter’s concept of embeddedness to examine how economic actions are socially embedded rather than autonomous. A qualitative approach with a descriptive-analytical design was employed from April 8, 2024 to January 9, 2026. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings indicate that the primary challenge lies not in food production itself, but in limited market access and unequal pricing structures. In response, farmers differentiate agricultural outputs for household consumption, social relations, and market distribution. The semi-organic system is applied selectively as an adaptive strategy, while cultural values remain the foundational framework guiding food farming practices within the community.